Pengaruh Konsentrasi Jus Bawang Putih (Allium sativum L.) Terhadap Karakteristik Fisik, Kimia dan Mikrobiologi Daging Babi - Putri Dewi, Gusti Ayu; Indri Hapsari Arihantana, Ni Made; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
Pork meat is one of the foods that is susceptible to contamination and damage caused by microbial growth that can affect the quality and safety of pork meat. Efforts can be made to maintain the quality and safety of pork meat by adding garlic juice that has antimicrobial content. This study was aimed to determine the effect of garlic juice concentration (Allium sativum L.) on the physical, chemical and microbiological characteristics of pork meat and to determine the right concentration of garlic juice (Allium sativum L.) in producing the best physical, chemical and microbiological characteristics of pork meat. This study used a complete randomized design consisting of 7 levels of garlic and aquadest comparison, that is without the addition of garlic and aquadest, 10:90, 20:80, 30:70, 40:60, 50:50 and 60:40. The treatment was repeated 3 times to obtain 21 experimental units. The data obtained was analyzed by variance and if the treatment had a significant effect then it was followed by Duncan's Multiple Range Test (DMRT). The results of this research showed that concentration of garlic juice (Allium sativum L.) had a significant effect on the physical characteristics namely water holding capacity (WHC), texture, pH, chemical characteristics namely moisture content, protein content, and microbiological characteristics namely TPC (Total Plate Count), Coliform and E. coli of pork meat. The ratio of 60% garlic and 40% of aquadest had the best pork meat characteristics with physical characteristics that is water holding capacity (WHC) 39.08%, texture 17.12 N, pH 5.79, chemical characteristics that is moisture content 73.25%, protein content 25.98% and microbiological characteristics that is 1.78 x 105 cfu/g Total Plate Count, 3.40 MPN/g Coliform and 0 cfu/g E. coli.